Nature pleated surfaces - Oliveira, M. J.; Osório, F. (Formal methods in architecture: Proceedings of the 5th International Symposium on Formal Methods in Architecture (5FMA), 2020)
This paper presents a concept design methodology that intends to enable us-ers to design a self-supporting structure based on the terrestrial plants’ bio-logical properties and on origami geometric principles that was tested on an eight-hour workshop at eCAADe/SiGraDi’2019 in Oporto. Focusing on rigid and flat-foldable origami surfaces the methodology invites its users to deal with several architectural aims, constraints and analysis based on the geomet-ric rules of this origami type. These surfaces behave in a particular way through folding, they depart from a planar state and after the folding process they arrive to a new planar state (flat-foldable Origami). If the faces remain rigid and flat during the folding process, the only change happens at the creases that behave as revolute joints. This way the folding of the surface is directly related to rigid kinematics allowing for a geometry based digital sim-ulation. After the aims, constraints and analysis definition, the methodology users are conducted through an abstraction process that explores the three fundamental forms of nature adaptation strategies – morphology, behavior and physiology, giving rise to a hybrid biological principle that will lead to the conceptual design process. The design process is conducted through analysis, experimentation with paper prototypes and the use of parametric design, enabling this way the emulation of the design process, where the functionality, geometry, robustness and aesthetics are tested and discussed.